Effect of Devices and Driving Pressures on Energy Requirements and Mass Transfer Coefficient on Microalgae Lipid Extraction Assisted by Hydrodynamic Cavitation - Martomo Setyawan; Panut Mulyono; Sutijan Sutijan; Yano Surya Pradana; Laras Prasakti; Arief Budiman (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
Previous studies of biodiesel production from microalgae have concluded that microalgal biodiesel is not profitable at an industrial scale due to its excessive energy consumption for lipid extraction. Hydrodynamic cavitation lipid extraction is one of the extraction methods which has lower energy consumption. Thismethod enables a fast extraction rate and low energy consumption for cell disruption. In order to achieve optimum process conditions, several influential parameters, which are cavitation generator geometry and driving pressure, need to be scrutinized. The experimental result showed that the maximum yield was obtained at 5 bar driving pressure. The lowest specific extraction energy was obtained at 4.167 bar driving pressure while using one side concave cavitation generator geometry with the ratio of the reduced cross-sectional area of 0.39. The value of the energy extraction requirement 17.79 kJoule/g lipids is less than the biodiesel heating value, and the value of the volumetric mass transfer coefficient is almost 20 times fold greater than the conventional extraction method, therefore this method is promising to be further developed.